Application of the Team Games Tournament (TGT) Type Cooperative Learning Model to Students’ Understanding of Concepts in Stationary Wave Material - Priandana, Afrian Azmi (Universitas Negeri Padang, 2024)
This research explains the application of the Team Games Tournament (TGT) Cooperative Learning Model on students' understanding of the concept of standing waves. The Teams Games Tournament (TGT) model is a team-based learning strategy where students are grouped into teams of four or five members of varying achievement levels. The steps involved in implementing the TGT cooperative model include class presentation, grouping, games, tournament, and team recognition. The research design used is Quasi Experiment with a quantitative approach. The subjects of this research were students of class XI science 4 using a purposive sampling technique. The research instrument includes multiple-choice questions in the form of pre-tests and post-tests, and data analysis techniques involved T-test and N-Gain analysis. The research findings indicate differences in student learning outcomes before and after the implementation of this model. Hypothesis testing using the T-test showed that the calculated tcount > ttable (11.000 > 2.262), thereby accepting the alternative hypothesis (H1). Additionally, the N-Gain results indicated a moderate improvement category. These results demonstrate that the Team Games Tournament (TGT) cooperative learning can enhance students' understanding of the concept of standing waves for the 11th-grade science class. In conclusion, the TGT learning model was perceived by students as an engaging and effective learning process that improves understanding of the standing waves concept.